Penyiaran dan Ketahanan Nasional: Studi Analisis Wacana Pemilu 2024 dalam Menjaga Integrasi Bangsa pada Talkshow Rosi - Zubairi, Ach. Ilham; Khoirul Fatih, Moh (ALAMTARA, 2024)
The Rise of Talk Shows and Their Role in Shaping Public Discourse: A Case Study of Rosi on Kompas TV. The Indonesian television landscape has undergone significant transformation in recent years, expanding from a single state-owned channel, Televisi Republik Indonesia (TVRI), to encompass eleven stations. This proliferation has led to a surge in programming diversity, with talk shows emerging as a popular genre. Among these, Rosi, a talk show aired on Kompas TV, a leading national news channel, has garnered notable public attention. Kompas TV's broadcasting serves as a platform for news and current affairs, reflecting the media's perspectives on general elections and national resilience. Rosi, a Kompas TV production, offers insights and perspectives on elections within the context of national integration. It underscores the role of elections as a tool for fostering collaboration among diverse elements of society to safeguard unity and cohesion.